If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -2) + -3(3x + 3) = -5 Reorder the terms: 2(-2 + 2x) + -3(3x + 3) = -5 (-2 * 2 + 2x * 2) + -3(3x + 3) = -5 (-4 + 4x) + -3(3x + 3) = -5 Reorder the terms: -4 + 4x + -3(3 + 3x) = -5 -4 + 4x + (3 * -3 + 3x * -3) = -5 -4 + 4x + (-9 + -9x) = -5 Reorder the terms: -4 + -9 + 4x + -9x = -5 Combine like terms: -4 + -9 = -13 -13 + 4x + -9x = -5 Combine like terms: 4x + -9x = -5x -13 + -5x = -5 Solving -13 + -5x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -5x = -5 + 13 Combine like terms: -13 + 13 = 0 0 + -5x = -5 + 13 -5x = -5 + 13 Combine like terms: -5 + 13 = 8 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6
| X-6y=11fory | | 93/8-62/4 | | f(x)-g(x)=0 | | 2(x+1)-3(x-2)=5-(x-1) | | 3/8/2/9 | | 4(x+3)=9x-7 | | 10x^2+105x+360=0 | | 4(x+3)=9x+7 | | 8-4x=13+x | | 3(x+7)=5x-9solve | | 18n^2-50=0 | | (3x-8)(-5)-(4-x)= | | 3(x+7)=5x-9 | | (-5/(2v-6))+4=6/(v-3) | | (2+3x)+62=90 | | (2+3x)+62=360 | | (2+3x)+62=180 | | 3(x+1)-2(x-1)=9 | | 5/3-1/6 | | x/7=47 | | x/-3=46 | | (x-24)+29+296=360 | | 4(2x-1)=2(3x-2) | | (3a/4)+5=(5a/6)+2 | | 3a/4+5=5a/6+2 | | (3x+18)93=180 | | (x+1)(x+11)=-14 | | 9+4lnx=14 | | w-4=3 | | (x^2-9)/(x+4)(x+3)=0 | | (2n+6)/3=((9n-4)/5)-n | | -2+15=17x-4-16x |